2011
DOI: 10.1002/mus.21851
|View full text |Cite
|
Sign up to set email alerts
|

Repeated courses of granulocyte colony‐stimulating factor in amyotrophic lateral sclerosis: Clinical and biological results from a prospective multicenter study

Abstract: Granulocyte colony-stimulating factor (G-CSF) induces a transient mobilization of hematopoietic progenitor cells from bone marrow to peripheral blood. Our aim was to evaluate safety of repeated courses of G-CSF in patients with amyotrophic lateral sclerosis (ALS), assessing disease progression and changes in chemokine and cytokine levels in serum and cerebrospinal fluid (CSF). Twenty-four ALS patients entered an open-label, multicenter trial in which four courses of G-CSF and mannitol were administered at 3-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Subsequently, a number of clinical trials have evaluated autologous MSC transplantation and demonstrated that intraspinal, intrathecal, and intracerebral transplants were safe and feasible [54]. It is worth mentioning that three clinical studies innovatively mobilized endogenous MSCs by using granulocyte-colony stimulating factor (G-CSF) in ALS patients, and their MSCs were instantaneously increased and no major adverse events were found in any of the three studies [55][56][57]. Moreover, BrainStorm Cell Therapeutics developed a cell type trademarked as "NurOwn™" for the treatment of ALS.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Subsequently, a number of clinical trials have evaluated autologous MSC transplantation and demonstrated that intraspinal, intrathecal, and intracerebral transplants were safe and feasible [54]. It is worth mentioning that three clinical studies innovatively mobilized endogenous MSCs by using granulocyte-colony stimulating factor (G-CSF) in ALS patients, and their MSCs were instantaneously increased and no major adverse events were found in any of the three studies [55][56][57]. Moreover, BrainStorm Cell Therapeutics developed a cell type trademarked as "NurOwn™" for the treatment of ALS.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Several small studies [20,21] have demonstrated feasibility of G-CSF administration without significant change in clinical outcome measured by the ALS functional rating scale. Preliminary diffusion tensor imaging results suggested white matter tract preservation with treatment [21].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Another study in 17 patients comparing subcutaneous G-CSF with a placebo control arm showed elevated CD34+ PBSCs, but no difference in disease progression [62]. Similarly, the STEMALS trial utilized subcutaneous G-CSF along with a 5-day course of mannitol with the hopes of increasing permeability across the blood-brain barrier in 26 patients [63,64]. Again, there was an increase in circulating CD34+ PBSCs, and in this trial a decrease in the proinflammatory cytokines monocyte chemoattractant protein-1 and interleukin-17, but no change in ALSFRS-R.…”
Section: Granulocyte-colony Stimulating Factor and Peripheral Blood Smentioning
confidence: 99%